Effects of the combination therapy of electric field stimulation and polyethylene glycol in the ex vivo spinal cord of female rats after compression. Issue 7 (12th April 2021) - Zhang, Cheng; Wang, Aihua; Zhang, Guanghao; Rong, Wei; Wu, Changzhe; Huo, Xiaolin
Abstract: The application of electric field stimulation (EFS) can reduce the cation influx after spinal cord injury. However, regenerated cation influx and reestablished injury potential are observed after EFS. Polyethylene glycol (PEG) is popular as an effective cell membrane fusion agent. This study aims to determine the effects of the combination therapy of EFS and PEG in the ex vivo spinal cord after compression. The ex vivo spinal cords of female rats with compression injury were incubated in a double sucrose gap recording chamber (DSGRC) and randomly divided into the following four groups: (1) compression group: compression only, (2) EFS group: EFS for 15 min, (3) PEG group: PEG treatment for 4 min, and (4) EFS + PEG group: EFS for 15 min and PEG treatment for 4 min. The hematoxylin–eosin staining was performed to measure the necrotic area of the spinal cords. The gap potential was detected, and the area under the curve of the gap potential was calculated. The intracellular cation concentration, membrane permeability, and compound action potential were measured and quantified. Results revealed no significant difference in the necrotic areas among different groups, and the compression model of the ex vivo spinal cord in the DSGRC had high consistency and stability. The combination therapy could attenuate cation inflow, promote cell membrane restoration, and promote the functional recovery of the spinal cord conduction after compression in ex vivo spinal cords. Abstract : In the present study, the effects of electrical field stimulation (EFS) and polyethylene glycol (PEG) were determined in the compression model of ex vivo spinal cords by using a double sucrose gap recording chamber (DSGRC). The effects of the combination therapy are better than those of the individual treatments of PEG and EFS. The methods of establishing ex vivo spinal cord compression model in the DSGRC can be useful in the fundamental and the clinical applications of the spinal cord injury in future.